Assessment on Cr, Cd, As, Ni and Pb uptake and phyremediation potential of Scirpus mucronatus (International Journal of Scientific Research and Management (IJSRM), 2017)
A laboratory experiment was conducted to examine the heavy metals (Cr, Cd, As, Ni and Pb) phytoaccumulation potential of an aquatic macrophytes Scirpus mucronatus. The macrophyte were transferred to the laboratory containing nutrient solution enriched with 1.0, 2.0, 4.0, 8.0 and 16 mg L-1 of Cr, Cd, As, Ni and Pb and were separately harvested after 2, 4, 6, 8 and 10 days. The bioaccumulation study showed a linear relationship for Cr accumulation but curvilinear in the case of the other metals with the exposure time (2–10 d). The accumulation of all the metals was found to be higher in the root than the shoot. The maximum bioconcentration factor (BCF) and translocation factor (TF) value were found in Pb (1387 and 0.95) and minimum BCF and TF values were found in Ni (386) and Cd (0.51) treated plants respectively. The experimental results demonstrated that the S. mucronatus can be used for removal of Cr, Cd and Pb from contaminated water.